INDUCTION OF OXIDATIVE STRESS BY ACUTE ORAL EXPOSURE OF CADMIUM CHLORIDE IN KIDNEY OF ADULT RAT - AMITA KUMARI,; RANJANA JHA, (The Bioscan, 2012)
Cadmium is a most abundant toxic heavy metal and an environmental pollutant. Oral administration of cadmium chloride (CdCl2) at a dose of 0.2 and 0.4% w/v with distilled water leads to significant (p<0.01) increase in lipid peroxidation and significant decrease in superoxide-dismutase (p<0.001), catalase (p<0.001) and glutathione- peroxidase (p<0.01) in the kidney of treated groups of rat as compared to control. Significantly higher level of lipid peroxidation and lower level of antioxidant enzymes (catalase, superoxide dismutase and glutathione-peroxidase) produces oxidative stress by disturbing the oxidative and antioxidative balance in the kidney of adult rats.